PENGEMBANGAN MEDIA POP UP BOOK BERBASIS INKUIRI PADA PEMBELAJARAN GEOMETRI RUANG DI KELAS V SD - Nazla Miranda Siregar,; Sukmawarti, Sukmawarti (Jurnal Cakrawala Ilmiah, 2024)
This development research aims to develop a product in the form of inquiry-based pop up book media in geometric learning that is suitable for use in the learning process. This research is a type of research and development (Research and Development) using the ADDIE development model which consists of 5 stages. However, in this study, researchers carried out the ADDIE development model only up to the 3rd stage, namely the development stage. The instrument used to collect data was a questionnaire or questionnaire given to several expert validators, namely the media expert validator, material expert validator and learning expert validator. Based on the validation results from the media expert validator, a score of 82 was obtained with the criteria of "Very Eligible". From the results of the material expert validation, a score of 88 was obtained with the criteria of "Very Eligible". From the results of the validation of learning experts, a score of 90 was obtained with the criteria of "Very Eligible". The average score from the assessment results of the three expert validators obtained a score of 86.6. Tracing the criteria for scoring scores, it can be said that inquiry-based pop up book media in geometric geometry learning developed is "Very Eligible" for use in the learning process.